Oseltamivir-resistant influenza A pandemic (H1N1) 2009 virus in Northern Greece - Gioula, G (LITHOGRAPHIA Antoniadis I.-Psarras Th. G.P., 2011)
Resistance to oseltamivir was observed to influenza A pandemic (H1N1) 2009 virus strains, isolated from two patients in North Greece. Investigations showed resistant viruses with the neuraminidase (NA) 275Y genotypes. Pandemic A (H1N1) 2009 virus should be closely monitored for emergence of resistant variants.